Incomplete pentalogy of Cantrell: a case report - Shenoy, Heera T.; Venugopal, Prasanna; S., Raghu; K., Remash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Pentalogy of Cantrell (PC) is a rare congenital anomaly characterized by a defect in the lower sternum, anterior diaphragm, and anterior abdominal wall; ectopia cordis; and congenital heart disease. Authors report a case of male foetus terminated at 20 weeks of gestation with an Incomplete (class 3) pentalogy of Cantrell presenting with gastroschisis, ectopia cordis and absence of lower sterna. Prognosis of pentalogy of Cantrell depends on severity of intra and extra cardiac defects, pulmonary hypoplasia, extent of abdominal wall defect, cerebral anomalies and diaphragmatic herniation. Full pentalogy of Cantrell is a severe and rare syndrome, but incomplete forms with combination of two or three defects are reported frequently similar to present case report. Early diagnosis through obstetric ultrasound would help in improved informed clinical decision making on the part of the obstetrician and family.